Characterization of cases of exogenous poisoning in adolescents in Brazil from 2014 to 2023: An ecological study (Research, Society and Development, 2024)
Objective: To describe reports of exogenous poisoning in adolescents in Brazil from 2014 to 2023. Method: Observational, ecological, descriptive, retrospective and quantitative study, using adolescents aged 10 to 14 years and 15 to 19 years, in the period 2014 to 2023, based on data collected through DATASUS through the Notifiable Diseases Information System. Results: There were a total of 292,823 cases of exogenous poisoning in adolescents between 2014 and 2023 in Brazil. It is noteworthy that the age group from 15 to 19 years old concentrates the majority of notifications (73.50%). Medications are the main cause (64.00%), followed by drugs of abuse (9.30%) and food and drinks (5.60%). As for the circumstances of the event, "self-medication" is a relevant circumstance, representing 12,288 cases, with a notable increase in the 15-19 age group. “Suicide attempt”, “abuse” and “accident” show significant incidences, with 179,227, 29,910 and 15,396 cases, respectively. Regarding evolution, the category of cure without sequelae revealed a predominance over the years, with 31,575 cases in 2023 (75.28%), contributing together with other categories to the complexity of these notifications. Conclusions: It is therefore necessary to understand the profile of cases, in order to support the implementation of intervention and prevention policies for this problem and, therefore, contain the exponential growth of these cases.